1958: Only world government can prevent the war nobody can win. (1st November 2020) - Russell, Bertrand
ABSTRACT: This is a speech that was to have been given to a nuclear disarmament campaign conference which was banned by the Swiss government. It was instead published in the September 1958 issue of the Bulletin . It is republished here as part of a special issue commemorating the 75 th year of the Bulletin .